Development of bioconjugate from streptomyces tyrosinase and gold nanoparticles for rapid detection of phenol constituents - Zainab, Mazhari Bi Bi; Madhusudhan, D. N.; Raghavendra, H.; Dastager, Syed Gulam; Dayanand, Agsar (Indian Journal of Experimental Biology, 2014)
Most of the phenol compounds are toxic and have been considered as hazardous pollutants. Several physicochemical and biological methods are available to detect and monitor the phenol pollutants in water and soil. In the present study, phenol constituents of winery, paper and plastic industrial effluents were successfully detected employing tyrosinase-gold nanoparticles bioconjugate. The synthesis of extracellular tyrosinase and gold nanoparticles was achieved by a single isolate of Streptomyces sp. DBZ-39. Enhanced production (369.41 IU) of tyrosinase was produced in submerged bioprocess employing response surface method with central composite design. Extracellular gold nanoparticles synthesized (12-18 nm) by Streptomyces sp. DBZ-39 were characterized with TEM, EDAX and FTIR analysis. A rapid detection (within 10 min) of phenol constituents from winery effluents was achieved by bioconjugate, when compared to tyrosinases and gold nanoparticles independently. Streptomyces tyrosinase could exhibit relatively a better performance than commercially available mushroom tyrosinase in the detection of phenol constituents. Winery effluent has shown much higher content (0.98 O.D) of phenol constituents than paper and plastic effluents based on the intensity of color and U.V absorption spectra.
Keywords: Bioconjugate; gold nanoparticles; Phenol detection; Streptomyces; Tyrosinase

Domibacillus enclensis sp nov., isolated from marine sediment, and emended description of the genus domibacillus - Sonalkar, Vidya V.; Mawlankar, Rahul R.; Krishnamurthi, Srinivasan; Tang, Shan-Kun; Dastager, Syed Gulam (International Journal of Systematic and Evolutionary Microbiology, 2014)
A novel red-pigmented bacterial strain, designated NIO-1016(T), was isolated from a sediment sample from Chorao Island, India and was investigated by a polyphasic taxonomic approach. The strain was Gram-reaction-positive, strictly aerobic, motile and catalase-positive and produced spherical to slightly ellipsoidal endospores with subterminal position on swollen sporangia. The genomic DNA G+C content was 46.9 molok. The major fatty acids were anteiso-C-15:0, anteiso-C-17:0, iSO-C-15:0 and C-16:0. The predominant quinones were MK-6 (89.3 %) and MK-7 (8.7 %). The polar lipids consisted of diphosphatidylglycerol, phosphatidylglycerol, and an unidentified phospholipid. meso-Diaminopimelic acid (type My) was present in the cell-wall peptidoglycan and the major whole-cell sugars were glucose and ribose. The closest phylogenetic neighbours were identified as Domibacillus robiginosus DSM 25058(T) (98.0% similarity) and Domibacillus indicus DSM 28032(T) (97.2% similarity), other species of the genus Bacillus displayed below 96% similarity. Phylogenetic, physiological, biochemical and morphological differences between strain NI0-1016(T) and its closest neighbours indicate that this strain represents a novel species in the genus Domibacillus in the family Bacillaceae for which the name Domibacillus enclensis sp. nov. is proposed with the type species N10-1016(T) (=DSM 25145(T)=NCIM 5462(T)=CCTCC AB 2011121(T)).

Deinococcus enclensis sp nov., isolated from a marine sediment sample - Thorat, Meghana N.; Mawlankar, Rahul R.; Sonalkar, Vidya V.; Ramana, V. Venkata; Joseph, Neeta; Shouche, Yogesh S.; Dastager, Syed Gulam (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2015)
A novel pale-pink coloured strain, designated NIO-1023(T), was isolated from a marine sediment sample from Chorao Island, Goa, India. The taxonomic position of strain NIO-1023(T) was investigated by using a polyphasic approach. The cells were observed to be Gram-stain positive, coccal shaped and non-spore forming. Phylogenetic analyses using the 16S rRNA gene sequence of the isolate indicated that the organism belongs to the genus Deinococcus. The strain NIO-1023(T) showed highest 16S rRNA gene sequence similarities with Deinococcus ficus (97.8 %), whereas other Deinococcus species showed less than 95 % sequence similarity. The DNA-DNA relatedness with respect to D. ficus CC-FR2-10(T) was 23.9 %. Chemotaxonomic data revealed that strain NIO-1023(T) contains only menaquinone MK-8 as the respiratory quinone and a complex polar lipid profile consisting of different unidentified glycolipids and polar lipids, two unknown phospholipids and three unknown phosphoglycolipids. As in other deinococci, one of these phosphoglycolipids was predominant in the profile. The predominant fatty acids were identified as C-17:1 w8c, C-16:1 w6c/w7c, C-15:1 w6c and C-17:1 w9c. The genomic DNA G + C content of strain NIO-1023(T) was determined to be 67.2 mol%. The biochemical and chemotaxonomic properties demonstrate that strain NIO-1023(T) represents a novel species, for which the name Deinococcus enclensis sp. nov. is proposed. The type strain is NIO-1023(T) (=DSM 25127(T) = NCIM 5456(T)).
Keywords: 16S rRNA; Deinococcus; Marine sediments; Polyphasic